"One Nature of the Word Enfleshed". (16th April 2015) - Edwards, Mark
Abstract : According to the least charitable view of Cyril's part in the "Nestorian controversy, " it was for him nothing more than that—a political scheme to eject a man whose scrutiny he had come to fear from a see whose power he had always envied. This account suggests that his apparent tergiversations tell us nothing of his theology: as a Christian he believed what the rest of Christendom believed, but as a prince of the church he turned his coat whenever this would serve to disguise his malice or change the wind. The more generous account reproaches Cyril not with bad faith but with bad logic: throughout his work, he oscillates between conflicting paradigms, in one of which the true subject of Christology is the Word who assumes the flesh, while in the other Christ has only the "compositional" unity that results from the coming together of two natures. The first prefigures the Chalcedonian shibboleth "one person in two natures"; the second Cyril himself encapsulated in the formula "from two natures, " which can be taken to entail that after the union there were no longer two natures but one. That Cyril himself drew this conclusion, contradicting the Chalcedonian Definition before he had heard it, is put beyond doubt for many by his defiant reiteration of a formula that he derived without knowing it from Apollinarius: "one nature [ phusis ] of the Word enfleshed."